The influence of laser powder-bed fusion microstructures on the corrosion behavior of CuSn alloy - Karthik G.M.; Haftlang F.; Kwak J.; Sathiyamoorthi P.; Zargaran A.; Kim Y.-T.; Kim H.S. (My University, 2025)
Selective laser melting (SLM), a laser powder-bed fusion technique, shows unique heterogeneous microstructures because of the complex thermal history they experience during layer-wise part fabrication. The current work attempts to establish the influence of these microstructures on the corrosion behavior of the SLM processed CuSn alloy. The as-built SLM samples showed heterogeneous epitaxial columnar grains, fine cellular dislocation structure (~ 600 nm) with cell boundaries having higher dislocation density and solute Sn concentration than the cell interior, super-saturated solid-solution with ~ 6.5 wt% of Sn in Cu, and fine second-phase δ (Cu41Sn11) ~ 200 nm. The SLM microstructures affected the corrosion behavior of the CuSn alloy: the as-built samples showed high corrosion rate than the post-SLM heat-treated fully recrystallized samples. The effects of the residual stresses, cellular segregation, and second-phase δ (Cu41Sn11) on the corrosion behavior are minimal. The dislocation density and distribution primarily control the corrosion behavior of the SLM processed CuSn alloy. The partially recrystallized microstructures with heterogeneous dislocation distribution showed an increased corrosion rate. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.